UiTM Terengganu Clinic Equipment Booking System (UCLEBS) / Norfadila Othman - Othman, Norfadila (2014)
Nowadays, peoples gained a lot of benefits from the application usage of Internet website and online reservation system. UiTM Terengganu Clinic Equipment Booking System (UCLEBS) was developed to integrate the booking system used by the staffs and students in UiTM Terengganu prepared using an intermediary approach. In order to ease in booking clinic equipment by providing a platform for made booking, to replace the manual booking to online booking and to provide an effective way to manage and organized the management flow of booking. The methodology used to develop UCLEBS was adapted and edited from Rapid Application Development (RAD) techniques where it is consists of five phases. The phases are requirements analysis, system design, system development, unit testing and integration testing that can do the backward process. UCLEBS were enable the student and staffs to register their account, update their profile and make booking of clinic equipment. Besides that, the administrator will control all the processes which are add, update, search and delete information. The evaluation techniques that had been used in complete the project were interview and distribute questionnaires to students and staffs in UiTM Terengganu. Results and finding from the evaluation clarified that users accept the system and belived that it was necessory to be used by students and staff in UiTM Terengganu (Mean=4.260, SD=0.769). The result illustrated the whole integrated system are well functioned. UCLEBS also establish the use of paperless and save time for students and staff to make a reservation clinic equipment. The UCLEBS can be improved in the future by other researchers in the user interface and functionality.